Survey of Economic Implications of Maritime and Territorial Disputes - Mendoza, Ronald U (Archīum Ateneo, 2019)
Drawing on studies on the economics of conflict, this paper reviews the literature on maritime and territorial disputes; and it examines an array of economic implications associated with territorial and maritime disputes. These include adverse effects on certain economic and development outcomes arising from possible armed confrontation, with some of these possibly lingering in the aftermath of conflict. There are also various economic disruptions and costs associated with these disputes, emphasizing how they also affect the livelihoods of resource users in the disputed areas. A clearer understanding of these economic links could help inform and motivate policymakers on mitigating the risks of conflict. Based on the review of evidence herein, the economic implications of conflict in terms of foregone average trade among the country pairs considered in the West Philippine Sea/South China Sea (in 1985 dollars) – which differ in important ways but hint at some common channels of impact – could range from US$ 909.3 million to US$ 98.8 billion. More broadly, the impacts on a disrupted global production chain can easily amplify these results even further, affecting global growth prospects for many decades, according to experience.